1988
DOI: 10.1161/01.cir.78.5.1192
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal I-123 metaiodobenzylguanidine myocardial washout and distribution may reflect myocardial adrenergic derangement in patients with congestive cardiomyopathy.

Abstract: 1-123 metaiodobenzylguanidine (MIBG) is a new radiopharmaceutical with properties that allow the characterization of the sympathetic innervation of several organ systems. In this study, we used MIBG with tomographic imaging to evaluate noninvasively the differences in myocardial sympathetic innervation in 14 healthy volunteers and 16 patients with severe dilated cardiomyopathy (CM). Initial (15-minute) images demonstrated no significant differences in MIBG concentration in the hearts of patients with CM and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
132
2
5

Year Published

1993
1993
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(142 citation statements)
references
References 17 publications
3
132
2
5
Order By: Relevance
“…20,21 However, in patients with ARVC, the present study and other reports 22 have shown that plasma catecholamines are not elevated. These findings suggest that increased synaptic norepinephrine confined to the heart 23 or enhanced myocardial sensitivity to catecholamines rather than elevated plasma levels may be responsible for increased sympathetic activity of the myocardium in ARVC.…”
Section: Increased Sympathetic Activitycontrasting
confidence: 48%
“…20,21 However, in patients with ARVC, the present study and other reports 22 have shown that plasma catecholamines are not elevated. These findings suggest that increased synaptic norepinephrine confined to the heart 23 or enhanced myocardial sensitivity to catecholamines rather than elevated plasma levels may be responsible for increased sympathetic activity of the myocardium in ARVC.…”
Section: Increased Sympathetic Activitycontrasting
confidence: 48%
“…Adrenergic presynaptic function was assessed by 123 I-metaiodobenzylguanidine ( 123 I-MIBG) imaging. 123 I-MIBG, a norepinephrine (NE) analog, is accumulated in sympathetic nerve endings through the uptake-1 mechanism and can be used to delineate cardiac sympathetic nerve distribution and function (21)(22)(23).…”
mentioning
confidence: 99%
“…24,25) A decrease in myocardial MIBG accumulation and NE has been reported in heart failure 21,[26][27][28][29] and also in experimental models of MI. 19,30) In the present study, it is unlikely that reduced MIBG accumulation and NE content would be due to sympathetic denervation by the surgical procedure because MIBG accumulation and NE content did not decrease in the sham-operated rats.…”
Section: Discussionmentioning
confidence: 92%